Histomorphometry evaluation and cellular proliferation in superficial corneal ulcer, induced in rabbits, after using eyedrops of Citrus lemon - Perches, C. S. [UNESP]; Pellizzon, C. H. [UNESP]; Ranzani, J. J. T. [UNESP]; Padovani, C. R. [UNESP]; Merlini, N. B. [UNESP]; Sereno, M. G.; Fonzar, J. F. [UNESP]; Brandao, C. V. S. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2015)
The aim of this study was to evaluate and compare through histomorphometry and immunohistochemistry for PCNA (Proliferating Cell Nuclear Antigen), the repair process in superficial corneal ulcers induced in rabbits and treated with eyedrops of Citrus lemon (CL) essential oil. Fifty female rabbits were used and divided into 4 experimental groups of 10 animals each one. Every animal underwent induction of experimental superficial ulcer by topical application of n-heptanol. Three groups were treated with eyedrops of Citrus lemon essential oil in two different concentrations: 3% (GL3) and 5% (GL5). Another group was treated with Tween 80 8% (GT), which is the solvent used in the production of eyedrops of CL; the control group (CG) received only tear substitute. All eyedrops were applied four times daily. The experimental groups were divided into two subgroups with five animals in each one, according to the final evaluation periods. The first subgroup (M1) was evaluated after 24 hours and the second (M2) after 5 days. In the comparison between the initial and final moments, the groups treated with tear substitute, Tween 80 8% and eyedrops of Citrus lemon essential oil 5% had an increase in epithelial thickness at the periphery of the cornea and a higher percentage of cell proliferation. There was no difference in cellularity between treatments. The eyedrops of Citrus lemon essential oil, at different concentrations, promoted corneal reepithelialization without causing further injury to the epithelium and corneal stroma, so they can be used on the ocular surface.
Keywords: sicilian lemon; cornea; ulcer; PCNA; histology